Approaches in the community schools of Urdaneta their implications to administrators - Alonzo, Adriano H. 1933- (1971)
The approaches applied by the community schools of Urdaneta in their rural education program and their implications to administrators were identified in this study. This study is significant because of its timeliness and relevance to the present direction of our educational goals. A knowledge of workable approaches that could be used as strategies in effecting rural education cannot be underestimated if the desired results in community education are to be expected.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Community and school; Education -- Philippines -- Urdaneta (Pangasinan).